Management of Vestibular Bone Fenestration with Periosteal Inhibition (PI) Technique During Alveolar Socket Preservation: A Case Report - Andrea Grassi; Maria Eleonora Bizzoca; Lucia De Biasi; Rossella Padula; Ciro Annicchiarico; Gabriele Cervino; Lorenzo Lo Muzio; Filiberto Mastrangelo (Medicina)
Background and Objectives: The purpose of this case report is to examine the management of vestibular bone fenestration during alveolar socket preservation using the Periosteal Inhibition (PI) approach. Here, for the first time, the PI technique, which has been shown to be successful in maintaining intact cortical bone, is examined in the context of a bone defect. Materials and Methods: After an atraumatic extraction of a damaged tooth, a vestibular bone fenestration was discovered in the 62-year-old male patient. To shield the defect, a non-resorbable PTFE membrane (OSSEO GUARD by Zimmer Biomet) was positioned between the mucosa and the fenestration site. A resorbable porcine gelatin sponge (SPONGOSTANTM) was used to achieve hemostasis, and a 5/0 PGCL absorbable suture was used to close the wound. A CBCT scan was performed, and a dental implant was inserted after 4 months. Results: After 4 months, the case demonstrated positive results, with full cortical remodeling and preservation of the original bone proportions. The fenestration completely healed, proving that the PI approach works even in the presence of bone flaws in cortical bone that is still intact. Conclusions: This is the first case report that shows that vestibular bone fenestration can be successfully treated with the PI approach. It has now been demonstrated that the procedure, which hitherto needed an undamaged cortical bone to work, can help bone abnormalities to repair completely. These results imply that the PI technique is a flexible and useful approach that provides predictable results in dental surgery for treating different types of alveolar bone abnormalities. Its use might be expanded with more study to include bone dehiscence treatment.